Role of Piccha Basti in the Management of Abnormal UterineBleeding – A Case Report - kaur, rajinder; Shukla, Seema; lata, Charu (International Research Journal of Ayurveda & Yoga, 2024)
The Ayurvedic classics mentioned various menstrual irregularities under the heading Artava vyapad. In this context, Asrigdara has been described by Acharyas as the excessive secretion of Rajas (menstrual blood) through vagina. Nowadays, a broader term abnormal uterine bleeding is used which describes irregularity in the menstrual cycle involving frequency, regularity, duration, and volume of blood flow. Acharyas described Asrigdar as Basti Sadhya entity and also advised to follow the treatment mentioned for Raktarsh, Raktatisar, and Raktapitta. Acharyas mentioned Piccha Basti as one of the treatment modality in these three diseases due to its Raktstambhan property. Hence, due to the same property, Piccha Basti can be used in Asrigdar also. The aim of the study was to evaluate the efficacy of Piccha Basti in the management of excessive bleeding per vaginum. In the present case, a female patient aged 42 years consulted PTSR OPD of Rajiv Gandhi Ayurvedic College and Hospital Distt. Kangra (H.P.) with the complaints of heavy menstruation and generalized weakness since 5 years. She was advised routine investigations and an ultrasound scan of pelvic organ to rule out any pathology and was planned for Piccha Basti and Narayan Tail Anuvasna in Yogbasti Krama after clearance of menses for 3 months. Pictorial blood loss assessment chart was used to assess the blood loss before and after treatment. The treatment showed highly satisfactory results in controlling the excessive bleeding during menstruation which was evident through the PBAC score. Piccha Basti is an effective treatment for the management of Asrigdar.